2017
DOI: 10.3390/ijms19010045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Botanical Origin and Chemical Composition on the Protective Effect against Oxidative Damage and the Capacity to Reduce In Vitro Bacterial Biofilms of Monofloral Honeys from the Andean Region of Ecuador

Abstract: Three types of monofloral honey from the Andean regions of Ecuador (Avocado, Eucalyptus, and Rapeseed honey) were analyzed to determine their floral origin, physicochemical parameters, chemical composition, antioxidant capacity, and their capacity to reduce in vitro bacterial biofilms. The chemical composition varied considerably depending on floral origin. The highest values of bioactive compounds were found in Avocado honey, classified as dark amber in color, while the lowest values were found in Eucalyptus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
3
12
1
Order By: Relevance
“…Phenolic compounds profiles are highly variable among different varieties of honey and specific floral markers of some monofloral varieties have been suggested [32][33][34]. These compositional variations could justify the differences in their bioactivity [17,35]. Previous studies confirmed that kynurenic acid and another unknown compound were present in higher concentrations in samples with a Castanea sativa origin [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds profiles are highly variable among different varieties of honey and specific floral markers of some monofloral varieties have been suggested [32][33][34]. These compositional variations could justify the differences in their bioactivity [17,35]. Previous studies confirmed that kynurenic acid and another unknown compound were present in higher concentrations in samples with a Castanea sativa origin [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…High resistance of bacterial biofilm was also confirmed in recent studies of Garcia-Tenesaca and coworkers. The dilution containing 20.0% of avocado honey eradicated about 60% of performed staphylococcal biofilm, and activity of eucalyptus and rapeseed honeys were even lower with the level of biofilm eradication below 50% [ 51 ]. Moreover, we observed that a concentration lower than MBEC 50 significantly enhanced the growth of the biofilm—honey probably is used as a source of glucose (easily digestible source of carbon).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, honey is regarded as potentially effective in the management of biofilm-associated infections: previous studies have demonstrated that honey may both hinder biofilm formation and reduce preformed biofilms ( Alandejani et al, 2008 ; Jervis-Bardy et al, 2011 ; Kilty et al, 2011 ; Maddocks et al, 2012 , 2013 ; Nassar et al, 2012 ; Majtan et al, 2014 ; García-Tenesaca et al, 2018 ). Here we showed that four honeys inhibit biofilm production by S. aureus , S. epidermidis , S. pyogenes , S. gordonii , and P. aeruginosa strains, and reduce preformed biomass without complete biofilm eradication.…”
Section: Discussionmentioning
confidence: 99%